Vaccines and Animal Models of Nipah Virus: Current Situation and Future Prospects - Chaoxiang Lv; Jiayue He; Qiqi Zhang; Tiecheng Wang (Vaccines)
Nipah virus (NiV) is a highly pathogenic paramyxovirus characterized by zoonotic infection, high mortality, and a lack of effective treatment, posing a serious threat to global public health security. Currently, it still lacks specific treatments or approved vaccines, and is listed as a potential pandemic threat pathogen by the World Health Organization. This paper systematically reviews the core progress and challenges of NiV investigation, with a focus on the development of animal models, vaccine development strategies, treatment strategy, and bottlenecks in translational medicine. Additionally, we discuss the strengths and limitations of existing animal models, including ferrets, hamsters, mice, and non-human primates (NHPs), and assess advances in vaccine platforms such as viral vectors, subunit vaccines, and mRNA-based vaccine candidates. The paper critically reviews the challenges facing translational research, conservation correlates, and outbreak preparedness, while also providing future research directions for pandemic preparedness and public health security strategies.